Microsoft New Future of Work Report 2022 - Teevan, Jaime; Baym, Nancy; Butler, Jenna; Hecht, Brent; Jaffe, Sonia; Nowak, Kate; Sellen, Abigail; Yang, Longqi; Ash, Marcus; Awori, Kagonya; Bruch, Mia; Choudhury, Piali; et al. (Microsoft, 2022)
Due to the “Great Remote Work Experiment” that began in March 2020 when workplaces around the world rapidly shut down, work is changing faster than it has in a generation. As many people now return to the workplace and begin to experiment with hybrid work, a range of different outcomes is possible. Thankfully, researchers at Microsoft and from around the world have been investigating evolving hybrid work practices and developing technologies that will address the biggest new challenges while taking advantage of the biggest new opportunities.​ This Microsoft New Future of Work Report 2022 summarizes important recent research developments related to hybrid work. It highlights themes that have emerged in the findings of the past year and brings to the fore older research that has become newly relevant. Our hope is that the report will facilitate knowledge sharing across the research community and among those who track research related to work and productivity. This research area is unfolding as rapidly as work is changing, and the purpose of this report is to help the community build on what has been learned this past year.​ Never before has there been such an opportunity to actively shape the future of work. With research and careful study, we can create a new future of work that is meaningful, productive, and equitable.